Effects of unilateral and bilateral vertebroplasty on coronal balance - Meral, Mehmet; Koç, Rahmi Kemal (The European Research Journal, 2025)
Objectives: Percutaneous vertebroplasty is frequently used to treat osteoporotic vertebral compression fractures (OVCFs) due to its low surgical risks. In this study, we tried to determine the early and late effects of single-pedicle and double-pedicle PVPs on the coronal balance of the vertebrae. Methods: This study evaluated 95 OVCF patients treated with PVP between 2008 and 2023. Of these patients, 36 were treated with bilateral and 59 with unilateral vertebroplasty. The Coronal Cobb angle, coronal segmental Cobb angle, and coronal balance of the vertebrae were measured in preoperative, early postoperative, and 6-month postoperative radiographs. The results were compared between the two groups and the effects of single or double pedicle procedure on these values were analyzed. Results: Two study groups were formed, consisting of a total of 95 patients. The mean age was 69.1 years. Fourty-nine patients were female and 46 were male. No significant difference was detected between the groups regarding gender and age. When the data obtained in the preoperative and early postoperative period in patients who underwent single and double pedicle vertebroplasty were evaluated, no statistically significant difference was obtained in coronal balance, Cobb angle, and segmentary Cobb angle measurements. Conclusions: From the radiographic point of view in the long-term follow-up, we think that bilateral PVP provides an advantage over the unilateral approach in maintaining the coronal balance and stabilization of the coronal Cobb angle in patients with OVCF.